Application of laboratory-result-oriented modular teaching model in the training of clinical hematology laboratory interns - Xie, Hui; Li, Jiale; Zhu, Yijia; Chen, Lin; Wang, Aofan; Gong, Linyan; Tan, Tingting; Wang, Xian; Chen, Yuxin (Frontiers in Medicine, 2025)
BackgroundCurrent teaching models for clinical hematology laboratory interns often prioritize theoretical knowledge dissemination over the practical application of skills directly tied to analyzing and interpreting laboratory results. This approach potentially limits the development of critical clinical reasoning and problem-solving abilities within the framework of quality management systems like ISO 15189. To address these challenges, this study implemented and evaluated a novel laboratory-result-oriented modular teaching model, explicitly integrating ISO 15189 principles. The study assessed the design, implementation, effectiveness, advantages, and challenges of this model compared to traditional methods.MethodsA total of 60 medical laboratory interns were recruited. Thirty interns completed their internship from October 2022 to March 2023 (control group), following the traditional model involving theoretical lectures supplemented by limited laboratory demonstrations. The remaining 30 interns undertook their internship from October 2023 to March 2024 (experimental group), receiving the laboratory-result-oriented modular teaching. Teaching effectiveness was compared through theoretical examinations, operational skill assessments, and satisfaction surveys.ResultsThe experimental group scored significantly higher than the control group in both theoretical examinations and operational skill assessments (p < 0.05). Their overall teaching satisfaction was also significantly higher (p < 0.05).ConclusionThe laboratory-result-oriented modular teaching model improved teaching effectiveness and fostered greater learning initiative among interns. It enhanced interns’ ability to analyze and solve problems independently and developed clinical reasoning skills.